2013
DOI: 10.1093/brain/aws359
|View full text |Cite
|
Sign up to set email alerts
|

Striatal allografts in patients with Huntington’s disease: impact of diminished astrocytes and vascularization on graft viability

Abstract: Neuronal transplantation has been proposed as a potential therapy to replace lost neurons in Huntington's disease. Transplant vascularization and trophic support are important for graft survival. However, very few studies have specifically addressed graft vascularization in patients with neurological disorders. In the present study, we analysed the vasculature of the host putamen and solid grafts of foetal striatal tissue transplanted into patients with Huntington's disease 9 and 12 years previously. Grafts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 41 publications
3
64
1
Order By: Relevance
“…Treating HD by transplanting solid fetal striatal tissue has been tested (Cisbani et al, 2013). The striatal grafts displayed significantly reduced numbers of large blood vessels and astrocytes, which may have contributed to the poor graft survival.…”
Section: Huntington Diseasementioning
confidence: 99%
“…Treating HD by transplanting solid fetal striatal tissue has been tested (Cisbani et al, 2013). The striatal grafts displayed significantly reduced numbers of large blood vessels and astrocytes, which may have contributed to the poor graft survival.…”
Section: Huntington Diseasementioning
confidence: 99%
“…Furthermore, histological studies in brain samples from HD patients, who had been transplanted with fetal striatal primordial tissue approximately 1 decade earlier to die, revealed a marked increase in atrophic astrocytes in the host brain surrounding the grafts, suggesting that a deficiency in host growth factors support, secreted by glia, may exacerbate the striatal neurons degeneration in HD (Cicchetti et al, 2011;Cisbani et al, 2013). So, in addition to the glutamate excitotoxicity theory for HD pathogenesis, a defective expression or activity of neurotrophic factors, such as BDNF and GDNF factors, may contribute to neuronal damage in HD (Giralt et al, 2010;Sarchielli et al, 2014;Wang et al, 2012;Zuccato et al, 2001;Zuccato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One post-mortem study from the Florida trial, 10-year post-transplantation, demonstrated graft survival with expression of markers of striatal projection neurons and interneurons and evidence of synaptic connections between transplanted neurons and host-derived dopaminergic and glutamatergic neurons, but also suggested some degeneration of grafted neurons [22]. A further post-mortem analysis from the Florida cohort, up to 12-year post-transplantation, observed that there were both fewer blood vessels and fewer astrocytes in the graft compared with the surrounding host tissue, which together may result in reduced trophic support to the graft and impact on graft survival [23]. However, these grafts also showed some typical striatal graft morphology in which there were regions of the grafts that were positive for AChE, termed p-zones, as well as areas with no expression of AChE, termed non-p-zones [23].…”
Section: Primary Foetal Tissuementioning
confidence: 98%
“…A further post-mortem analysis from the Florida cohort, up to 12-year post-transplantation, observed that there were both fewer blood vessels and fewer astrocytes in the graft compared with the surrounding host tissue, which together may result in reduced trophic support to the graft and impact on graft survival [23]. However, these grafts also showed some typical striatal graft morphology in which there were regions of the grafts that were positive for AChE, termed p-zones, as well as areas with no expression of AChE, termed non-p-zones [23].…”
Section: Primary Foetal Tissuementioning
confidence: 99%
See 1 more Smart Citation